Respuesta :
Answer: [tex]\text{ D) } 9.72[/tex]
Step-by-step explanation:
Here the give expression is,
[tex]2.7 \times(-3)\times (-1.2)[/tex]
We can write,
[tex]2.7 \times(-3)\times (-1.2) = 2.7 \times 3.6[/tex] ( because [tex]-a\times -b = ab[/tex])
[tex]2.7 \times(-3)\times (-1.2) = 9.72[/tex]
⇒ Option D is correct.
Answer:
D. 9.72
Step-by-step explanation:
We are given the following expression and we are to multiply it:
2.7 × (–3) × (–1.2)
Multiplying 2.7 and (–3) , starting from the left to get:
2.7 × (–3) = –8.1
Then multiplying this product with (–1.2) to get:
–8.1 × (–1.2) = 9.72
Since both of the terms were negative here so when negative is multiplied with another negative, it becomes positive.
Therefore, the correct option is D. 9.72.